Ethical Exercise of Leadership in A Synodal Church - Josin George Kaithakulam (Asian Horizons, 2025)
The less synodality, pertaining to participation and fraternity, is understood, the more it is talked about. With its democratic face, synodality calls for a change in the style of doing and leading. It is walking together that mutual understanding and appreciation of both—the leading and the lead—takes place. Its purpose is not to win over the other or outshine the other, but the common good—the reason behind the talk of synodality. The paper makes attempt to explain synodality in the primary context of ecclesial leadership. The Christian perspective of leadership becomes ethical only when leadership is redefined as serving the good of everyone at stake that prerequisites openness and humility. The missionary discipleship is the criterion of judging how synodal we are that our focus is more on ministering than administering. This mission is the source and end of synodal leadership. Therefore, synodal leadership invokes to rectify the exercise of authority as supressing the other, or its style domineering that might have affected fraternity, equality, and impartiality endangering the shepherding envisaged by Jesus.